Faktapremissi ja normipremissi: dualismista kohti holistisempaa oikeudellisen argumentaation teoriaa - Aalto-Heinilä, Maija; Paso, Mirjami (Lakimies, 2024)
Facts and norms: from a dualistic to a more holistic theory of legal argumentation The structure of a legal decision is often represented by means of a syllogism in which the legal conclusion is deduced from the norm premise and the fact premise. In the theory of legal argumentation, the main focus has been on how the norm premise can be specified by means of different methods of interpretation. Less attention has been paid to the construction of the fact premise, and discussions regarding the evaluation of evidence are typically kept separate from theories of legal interpretation. In our article, we bring these two equally important parts of legal decision-making under the same umbrella and point out some ontological and epistemological similarities between questions of law and questions of fact. This is not meant to dismiss the practical function of the law/fact distinction: it is important especially with regard to the structuring and organising of court proceedings. However, recognising similarities between the formation of the norm premise and the fact premise may have an impact on how the nature of legal dogmatics is understood, as well as make us aware of the epistemic risks involved in both stages. We conclude our article by encouraging legal scholars from different fields to co-operate in the development of more holistic approaches to legal thinking, in which norms and facts are viewed from a more general perspective.